2020
DOI: 10.7861/clinmed.2020-0322
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement in Atrial Fibrillation detection after ischaemic stroke (QUIT-AF)

Abstract: Background Paroxysmal atrial fibrillation (PAF) is a frequent cause of recurrent stroke but can be difficult to detect because of its episodic and often asymptomatic nature. We sought to improve rate of PAF detection through a quality improvement project (QIP) to deliver early prolonged inpatient cardiac monitoring on the stroke unit (SU). Methods A structured protocol for cardiac monitoring using 5-day event recorders was established. 'In-house' cardiac monitoring was implemented. Performance data on this cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…In patients with new AF detected, the provision of 'inhouse' monitoring significantly reduced the time of stroke/TIA onset to oral anticoagulant commencement from 41 (Phase 1) to 14 days (Phase 2) (Figure 5), p < 0.01 compared to Phase 1. Of the 17 new cases in Phase 2, the majority (10) were detected between days 0 and 2 after stroke/TIA (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with new AF detected, the provision of 'inhouse' monitoring significantly reduced the time of stroke/TIA onset to oral anticoagulant commencement from 41 (Phase 1) to 14 days (Phase 2) (Figure 5), p < 0.01 compared to Phase 1. Of the 17 new cases in Phase 2, the majority (10) were detected between days 0 and 2 after stroke/TIA (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our AF detection rate is also comparable to a smaller sized QIP, 'Quality Improvement in Atrial Fibrillation Detection after Ischaemic Stroke' study which reported AF detection rate of 14.7%. 10 A higher rate of AF detection was demonstrated with more prolonged cardiac monitoring post-stroke, for example, 'The 30-Day Cardiac Event Monitor Belt for Recording Atrial Fibrillation after a Cerebral Ischemic Event (EMBRACE)' trial found AF in 16% of people in the prolonged cardiac monitoring group. 8 There were 413 patients with stroke/TIA who passed through the acute stroke unit QEUH, with 59% of patients undergoing cardiac monitoring in Phase 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bravata 2 Kamal 31 Levi 32 Sui 33 Chiu 34 Klingner 35 Hill 36 Droegemueller 37 Pines 38 Wharton 39 Kishore 40 Hospital engagement…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Implementation of a pediatric stroke protocol over 7 years improved the use of magnetic resonance imaging (68%–78%) and increased National Institutes of Health Stroke Scale documentation (42%–82%). 39 Kishore et al 40 used an educational intervention (didactic session and hands on practice with simulation) to improve the detection of atrial fibrillation in 112 patients with stroke by ensuring delivery of early cardiac monitoring (20%–66%).…”
Section: Implementation Via Qi Interventionsmentioning
confidence: 99%